Environmental education: Curriculum guide for primary and lower secondary grades in the Caribbean - Glasgow, Joyce Louise (UNESCO, 1994)
This documentation is intended primarily for use by teachers of children in Caribbean schools at the lower primary grades 1-3 (ages 6-9 years), upper primary grades 4-6 (ages 9-12 years), and lower secondary grades 7-9 (ages 12-15 years). In preparation for its development, the existing curricula for primary and lower secondary levels in four Caribbean territories were analysed, in order to identify content and concepts with a bearing on environmental education (EE) already in the curricula, which would lend themselves to a further input of EE. A detailed summary of the analyses is presents in the appendix. The material is presented in six chapters: Chapter 1 places the material in context; Chapter 2 briefly discusses the approach for implementation of EE in the curricula; Chapter 3 provides background content for the teacher, under the content headings suggested by the analysis of the curricula; Chapter 4 deals with methodology, including ideas on learning resources, Chapter 5 presents the lesson exemplars; and Chapter 6 briefly addresses evaluation in EE. A glossary of environmental terms and a bibliography are also included.
Keywords: Environmental education